Improving Tomato Growth with Plastic Bottle Drip Irrigation in a Small Farming Framework - , Nidhi Singh, Rajul Soni, Girish Patidar, Teena Patidar, Aaradhana Patel, Mohit Pagare, Sachin Patel (Archives of Current Research International, 2025)
The current study involves developing a simple drip irrigation system using plastic bottles for the cultivation of tomatoes under a natural farming system. A simple and user-friendly installation process was developed using one-liter waste plastic bottles and medical syringes. Bio-composting of kitchen waste was done to provide nutrients to tomato plant. Neem tea was prepared from neem leaves and applied to enhance crop immunity. The highly efficient and precise irrigation system was implemented with the use of 15 litres of water per plant using 525 liters of water for a plot of 35 plants. Positive and good growth in tomato plants under drip irrigation was observed with respect to different agro-morphological observations including plant height, number of branches per plant, number of clusters per plant and number of fruits per plant. The treated tomato plot yielded 5 kg more fruits in comparison to the flooded plot. With an input cost of ₹710, the output was calculated at 60 kg of tomatoes, priced at ₹30 per kg, resulting in a total of ₹1800. The present research experiment provided a cost-effective and profitable plastic bottle drip irrigation system.